A wealth tax on the rich to bring down public debt? Revenue and distributional effects of a capital levy - Stefan Bach; Martin Beznoska; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The idea of higher wealth taxes to finance the mounting public debt in the wake of the financial crises is gaining ground in several OECD countries. We evaluate the revenue and distributional effects of a one-time capital levy on personal net wealth that is currently on the German political agenda. We use survey data from the German Socio-Economic Panel (SOEP) and estimate the net wealth distribution at the very top, based on publicly available information about very rich Germans. Since net wealth is strongly concentrated, the capital levy could raise substantial revenue, even if relatively high personal allowances are granted. We also analyze the compliance and administrative costs of the capital levy.
Keywords: H24; D31; H22; 330; capital levy; wealth distribution; microsimulation; Vermögensteuer; Reichtum; Wirkungsanalyse; Öffentliche Einnahmen; Verteilungswirkung; Mikrosimulation; Deutschland